Answer:
![((x-1)^2)/(9)-((y-2)^2)/(4)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/bsi8cl8pbj2s6j7hfgigocn7rlmg94bxvg.png)
Explanation:
Given equation:
![4x^2-9y^2-8x+36y-68=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/shhn157eyukqzu16gzs1ytbyzekwfnuioo.png)
This is an equation for a horizontal hyperbola.
To complete the square for a hyperbola
Arrange the equation so all the terms with variables are on the left side and the constant is on the right side.
![\implies 4x^2-8x-9y^2+36y=68](https://img.qammunity.org/2023/formulas/mathematics/high-school/dcyevz8yy7mhkeut7fasw8t9gha5zke3px.png)
Factor out the coefficient of the x² term and the y² term.
![\implies 4(x^2-2x)-9(y^2-4y)=68](https://img.qammunity.org/2023/formulas/mathematics/high-school/t79dhnzaqhw4r1im3x4jdybswendaykn41.png)
Add the square of half the coefficient of x and y inside the parentheses of the left side, and add the distributed values to the right side:
![\implies 4\left(x^2-2x+\left((-2)/(2)\right)^2\right)-9\left(y^2-4y+\left((-4)/(2)\right)^2\right)=68+4\left((-2)/(2)\right)^2-9\left((-4)/(2)\right)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/9b1ya29afe8nskgxqvd6g7lsvwmsen593a.png)
![\implies 4\left(x^2-2x+1\right)-9\left(y^2-4y+4\right)=36](https://img.qammunity.org/2023/formulas/mathematics/high-school/kgdpalamayf5easp4y3jwybeq336w1whfe.png)
Factor the two perfect trinomials on the left side:
![\implies 4(x-1)^2-9(y-2)^2=36](https://img.qammunity.org/2023/formulas/mathematics/high-school/k7ci7c3987jdada594ova8ycs6bc7sck9o.png)
Divide both sides by the number of the right side so the right side equals 1:
![\implies (4(x-1)^2)/(36)-(9(y-2)^2)/(36)=(36)/(36)](https://img.qammunity.org/2023/formulas/mathematics/high-school/3fhbmubkddhu01xmyvpxoa9rx4ermagyj3.png)
Simplify:
![\implies ((x-1)^2)/(9)-((y-2)^2)/(4)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/8f48d258qtuh1b5k8d9mey4xbp4id6vh3v.png)
Therefore, this is the standard equation for a horizontal hyperbola with:
- center = (1, 2)
- vertices = (-2, 2) and (4, 2)
- co-vertices = (1, 0) and (1, 4)
![\textsf{Asymptotes}: \quad y = -(2)/(3)x+(8)/(3) \textsf{ and }y=(2)/(3)x+(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/luacrsjna10usyzk16pnxapm2rvwm3azbd.png)
![\textsf{Foci}: \quad (1-√(13), 2) \textsf{ and }(1+√(13), 2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/h53pjgina0ubxofrztcjk7c5tbjiucchn1.png)